Contemporary Geographical Thought Essay - Dumin, Yuli (Postgraduate School, Universitas Nusa Cendana, 2024)
Several fundamental and contemplating questions have been evolving in my mind since I decided to devote my education and career path to the geography discipline. These questions are, “What is geography? What makes geography distinct from other disciplines? What can make us geographers survive in this inevitably changing world? And what will we geographers be in the future?”. These questions were not taken for granted; they are manifestations of my reflection of the time I spent as a geography teacher. It is obvious that geography’s existence as a subject in the curriculum system is not as popular as its counterpart in social science subjects such as economics and history. This is a consequence of the terms that Shore and Wright (2017:1, as cited in LahiriDutt, 2018) demonstrate as “academic capitalism” that places the concept of neoliberalisation as university policies. This context of capitalism in higher education led to a catastrophic impact for geography (Castree, 2006, as cited in Lahiri-Dutt, 2018). Back again to the initial fundamental questions, what is geography? I believe there is no one standardized definition of geography. This is because Geography is a pluralistic and multidisciplinary field of study with no homogenized perspective or one primary philosophical approach because it is a confluent discipline (Colwell, 2004; Mitchell & Murphy, 1991). This plurality has been constructed over time from the beginning geography was declared as a discipline to the contemporary geography. The diversity of subdisciplines in geography was started at the beginning of the twentieth century, when it was divided into two divisions:” physical and culture geography, and regional and systematic geography” (Mitchell & Murphy, 1991, p.58). Similarly, Hanson (2008) demonstrated that during the twentieth century the concept of geography popularised by William Morris Davis: “the impact of the physical (‘‘inorganic’’) environment on the biological (‘‘organic’’) environment” (p.717), which become popular around geographer authors in the earliest Annals of Association of American Geographers (AAG) in the earliest twentieth century, had been challenged by the emergence of economic geography before the end of twentieth century because at this time, human beings was acknowledged as agent who contribute to the development of their physical surroundings. However, as geography knowledge expands, there is a possibility for us to become more specialized. Specialization in geography (physical and human geography) can have positive and negative impacts. Philips (2004) explained, on the one hand, by specialization, we have the opportunity to collaborate with different scientists, which can contribute to the promising advantage. On the other hand, disintegration may lead to ineffective communication within and between specialist groups because there is no such a common thing that can become a core base knowledge. The next question to answer is what makes geography unique and survive as a discipline? Should we “geographers” disintegrate or integrate? I believe what makes geography distinct to other knowledge is its plurality, however, what makes geography can survive as a plural and diverse subject is the inclusive and collaborative work between physical and human geography. Therefore, I argue that the synergy between physical and human geography is crucial in geography knowledge development. In this essay, I will first demonstrate the history of geography and the key characteristics of human and physical geography which may lead to the integration or disintegration between them. Then, I analyse on how to develop the integration between human and physical geography from a philosophical and institutional perspective.